Dermatoplasty for decompensated forms of varicose veins and post-thrombotic syndrome - V. I. Rusin; F. M. Pavuk; I. I. Kovalchuk; O. A. Nosenko (Сучасні медичні технології)
Objective(s). In order to improve the results of the treatment of the decompensated form of varicose veins and post-thrombotic syndrome, taking into account the angiosomal theory and using VAC and Magott therapy of the recipient woundof the trophic ulcer, evaluate different methods of dermatoplasty depending on the depth and area of the lesion.